Analysis and Comparison of Characteristics for Offline PD Measurements in Turbo-Generators at Different Test Time Intervals - Dorkmai, K.; Pannil, P.; Tattiwong, K.; Maneerot, S.; Suksawat, D.; Pattanadech, N. (My University, 2022)
Partial discharge (PD) measurement is widely used for the condition assessment of high voltage equipments. It is a tool to detect the localized discharges occurring in the weakness point sites, which causes deterioration that can lead to failure. Hence, it is essential to diagnose the PD behavior to prevent the consequent failure which maybe takes place. This paper presents an analysis of the offline PD measurements performed on the stator winding insulation system of three turbo-generators which consist of a hydrogen-cooled generator rate of 211.75 MVA, 15.75 kV, and two air-to-water heat-cooled generators which the same rate of 50.8 MVA, 11.5 kV, which were located in the power plant. Firstly, the offline PD measurements of these generators have been energized to the star point side and the high voltage coupling capacitor is installed on the high voltage terminal side, according to IEC 60034-27-1. Additionally, the test voltages were applied to the test object with a step voltage profile. To analyze the PD behaviors of the stator winding insulation, the PD characteristics such as the PD pulses, PD magnitude, and phase-resolved PD (PRPD) patterns were monitored and recorded. Besides, the effect of applied test voltage-time, i.e., 1, 3, and 5 minutes, on such characteristics were reported and compared. Finally, the PD behavior of the stator winding insulation of these generators showed clearly different results for PD measured at different recording times. The highly fluctuating PD magnitude and PD pulse shape at the initial duration of the measurement, and then gradually decreases to convergence to a stable charge magnitude as the test-time increases.
Keywords: Different test time; Partial discharge; PD in rotating machine; PD test time interval; Turbo-generators